LDL atherogenicity determined by size, density, oxidation, apolipoprotein(a), and electronegativity: an updated review - Akyol, Omer; Chiang, Huan-Hsing; Burns, Alan R.; Yang, Chao-Yuh; Woodside, Darren G.; Sawamura, Tatsuya; Sánchez-Quesada, José Luis; Gotto, Antonio M.; Chen, Chu-Huang (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerotic cardiovascular disease (ASCVD), including coronary heart disease and cerebrovascular disease, is caused by the accumulation of plaque on artery walls. Elevated levels of low-density lipoprotein (LDL) cholesterol significantly contribute to the development and progression of ASCVD. Multiple studies have provided evidence of a correlation between individual LDL subpopulations and the development of atherosclerosis (AS); among these, small, dense low-density lipoprotein (sdLDL) and lipoprotein(a) [Lp(a)] have been particularly implicated. There are multiple considerations of why sdLDL may cause AS including their low affinity for the LDL receptor, their ability to diffuse into the artery wall and remain there for a long time, and their tendency to become excessively oxidized. Oxidized LDL (oxLDL), generated under oxidative stress, drives AS by impairing endothelial function, promoting foam cell formation, and triggering vascular inflammation. Lp(a) contributes to the development and progression of AS by causing inflammation of the arterial wall. Studies conducted in recent years have found that electronegative LDL [L5/LDL(-)] may also be an important factor in the development and progression of AS. L5/LDL(-) causes atherosclerotic changes in the vascular wall by triggering apoptosis in endothelial cells via the lectin-like oxLDL receptor-1. This article offers an updated overview of ASCVD and briefly examines the classifications of atherogenic LDL subfractions and their roles in atherogenesis.